Kelimpahan dan Keanekaragaman - Ilmy Amalia; I Wayan Restu; Endang Wulandari Suryaningtyas (Fakultas Kelautan dan Perikanan Universitas Udayana, 2020)
Serangan Island is a strategically touristic beach area where there is a vast expanse of seagrass being cultivated as habitat for the epiphuna, the beach has tourism activities such as surfing and swimming which could affect the life of epiphuna. The purpose of this study is to know the abundance and diversity of epiphuna in the seagrass area using the 1x1 m quadrat transect method. The study was conducted in February 2017. The highest epiphuna abundance at location 1 was 25,1 ind/m2. The lowest abundance value is at location 2 which is 19,1 ind/m2, whereas at location 3, it has the abundance value of 21,1 ind/m2. The epiphuna species that dominates from all three locations are from the Arthropoda phylum including Clibanarius taeniatus, Coenobita sp. and Calcinus laevimanus. The highest diversity index was found in location 1, 2,211, location 2 was 2,132 and the lowest was at location 3 which was 1,853, while the highest seagrass density of the three stations was Syringodium isoetifolium type 358 stands/m2 and the lowest was Thallasodendron ciliatum, 29 stands/m2. The results of the overall water quality measurement, ie, the temperature ranged from 27,6 to 28,40C, the pH ranged from 7,7 to 7,9, the salinity ranged between 28-30 ppt and DO ranged between 4,5-4,7 mg/l. Serangan Island coastal waters have the highest abundance of epiphuna in Arthropoda phylum, moderate (location 1 and 2) and low (location 3) diversity level, and with a normal water quality which is feasible for epiphuna life.